Ethnobotanical survey on medicinal plants from Milos island (Kiklades Islands, Greece) - Perouli, Mary; Bareka, Pepy (Mediterranean Botany, 2022)
Milos is a volcanic island in Greece, isolated from the mainland since its birth 480.000 years ago. The present study provides information on plant species used for medicinal purposes by indigenous people during 16th to 21st century. The aim of the study was to collect, preserve and elaborate data on pharmaceutical plants used by Milos’ inhabitants, to find new plants used in traditional medicine or new uses of the already known ones and to reveal and explain changes of medicinal plants used through 16th to 21st centuries. Data on plant species, for other purposes, except eating, were also collected. Additionally, the data collected were compared to previous literature in order to explain the changes in phytopharmaceutical approaches on the island during 16th to 21st centuries. The research was based on interviews of inhabitants, concerning medicinal plant species used in 20th and 21st centuries, on an unpublished manuscript and on local, folk literature on pharmaceutical plant species during 16th and 19th centuries.